Environmental performance of electricity storage systems for grid applications, a life cycle approach. (1st September 2015) - Oliveira, L.; Messagie, M.; Mertens, J.; Laget, H.; Coosemans, T.; Van Mierlo, J.
Highlights: Large energy storage systems: environmental performance under different scenarios. ReCiPe midpoint and endpoint impact assessment results are analyzed. Energy storage systems can replace peak power generation units. Energy storage systems and renewable energy have the best environmental scores. Environmental performance of storage systems is application dependent. Abstract: In this paper, the environmental performance of electricity storage technologies for grid applications is assessed. Using a life cycle assessment methodology we analyze the impacts of the construction, disposal/end of life, and usage of each of the systems. Pumped hydro and compressed air storage are studied as mechanical storage, and advanced lead acid, sodium sulfur, lithium-ion and nickel–sodium-chloride batteries are addressed as electrochemical storage systems. Hydrogen production from electrolysis and subsequent usage in a proton exchange membrane fuel cell are also analyzed. The selected electricity storage systems mimic real world installations in terms of capacity, power rating, life time, technology and application. The functional unit is one kW h of energy delivered back to the grid, from the storage system. The environmental impacts assessed are climate change, human toxicity, particulate matter formation, and fossil resource depletion. Different electricity mixes are used in order to exemplify scenarios where the selected technologies meet specific applications. Results indicate that the performance of the storage systems is tied to the electricity feedstocks used during use stage. Renewable energy sources have lower impacts throughout the use stage of the storage technologies. Using the Belgium electricity mix of 2011 as benchmark, the sodium sulfur battery is shown to be the best performer for all the impacts analyzed. Pumped hydro storage follows in second place. Regarding infrastructure and end of life, results indicate that battery systems have higher impacts than mechanical ones because of lower number of cycles and life time energy.